2021
DOI: 10.1016/j.jobcr.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary management of skull base surgery

Abstract: Skull base surgery remains one of the challenging areas in the field of cranio-maxillofacial surgery, otolaryngology and neurosurgery. Subsequent reconstruction of bone and soft tissue are an essential component to restore function and appearance after ablative surgery.Establishment of interdisciplinary tumor boards with presentation of the individual patient cases have become standard. Multiplanar reconstruction using MRI or CT imaging techniques combined with virtual 3D planning allow precise planning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Skull base surgery has long been a challenging area of anatomy. Multiplanar reconstruction with MRI or CT imaging combined with virtual 3D planning is now increasingly used in skull base surgery to achieve accurate preoperative planning and to assist the surgeon in the actual clinic with CADIN to remove or sample lesions within safe limits that are di cult to reach without extensive surgical exposure (Rothweiler et al 2021). 2021) retrospectively analyzed data from seven patients who used a combination of mixed reality and surgical navigation to assist in oral and maxillofacial tumor surgery and evaluated the feasibility and accuracy of the protocol.…”
Section: Skull Base Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Skull base surgery has long been a challenging area of anatomy. Multiplanar reconstruction with MRI or CT imaging combined with virtual 3D planning is now increasingly used in skull base surgery to achieve accurate preoperative planning and to assist the surgeon in the actual clinic with CADIN to remove or sample lesions within safe limits that are di cult to reach without extensive surgical exposure (Rothweiler et al 2021). 2021) retrospectively analyzed data from seven patients who used a combination of mixed reality and surgical navigation to assist in oral and maxillofacial tumor surgery and evaluated the feasibility and accuracy of the protocol.…”
Section: Skull Base Surgerymentioning
confidence: 99%
“…The use of CADIN can provide an accurate and clear indication of foreign body and tumor boundaries. This allows the surgeon to perform accurate removal of foreign bodies and tumors without frequent intraoperative review of preoperative medical images, greatly improving the safety and accuracy of the procedure(Sukegawa et al 2018;Ji et al 2018;Rothweiler et al 2021).…”
mentioning
confidence: 99%
“…A multidisciplinary approach is fundamental for the best outcome in treating skull base diseases. This can be coordinated through a Multidisciplinary Skull Base Board (MDT-SB), where all physicians involved in patient care, both surgeons and non-surgeons, participate [3]. It has been found that the patient care approach can differ in more than a tenth of cases after MDT-SB consultation compared to care without MDT-SB presentation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The SOFF, on the other hand, is used preferably for the reconstruction of the temporomandibular joint, as the scapular tip can be used for anatomical replacement of the condylar head. Moreover, by raising the latissimus dorsi muscle, a high volume of soft tissue can be harvested alongside the SOFF [ 18 , 19 ]. The DCIA graft provides anatomically shaped bone with sufficient vertical height resembling the anatomical form of the mandibular body [ 20 ].…”
Section: Introductionmentioning
confidence: 99%